2013
DOI: 10.1038/onc.2013.476
|View full text |Cite
|
Sign up to set email alerts
|

Protumorigenic effects of mir-145 loss in malignant pleural mesothelioma

Abstract: We identified a discrete number of microRNAs differentially expressed in benign or malignant mesothelial tissues. We focused on mir-145 whose levels were significantly downregulated in malignant mesothelial tissues and Malignant pleural mesothelioma (MPM) cell lines as compared to benign tissues (pleura, peritoneum or cysts). We show that promoter hyper-methylation caused very low levels in MPM cell lines. Treatment of MPM cell lines with mir-145 agonists negatively modulated some protumorigenic properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 56 publications
6
82
0
Order By: Relevance
“…miRNAs, which usually induce gene silencing, can function as either tumor suppressors or oncogenes (17). Recent studies have identified several miRNAs with diagnostic, prognostic and therapeutic potential in pulmonary malignant diseases including NSCLC and MPM (18)(19)(20)(21). For example, the identification of low levels of miR-29c in MPM has provided both a new prognostic tool and has pointed to aberrant chromatin methylation as being involved in progression of the disease (20).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…miRNAs, which usually induce gene silencing, can function as either tumor suppressors or oncogenes (17). Recent studies have identified several miRNAs with diagnostic, prognostic and therapeutic potential in pulmonary malignant diseases including NSCLC and MPM (18)(19)(20)(21). For example, the identification of low levels of miR-29c in MPM has provided both a new prognostic tool and has pointed to aberrant chromatin methylation as being involved in progression of the disease (20).…”
Section: Introductionmentioning
confidence: 97%
“…For example, the identification of low levels of miR-29c in MPM has provided both a new prognostic tool and has pointed to aberrant chromatin methylation as being involved in progression of the disease (20). A recent study demonstrated that loss of miR-145 affects tumorigenic properties of MPM cell lines (21). These findings have prompted the study of miRNA expression levels as potentially important diagnostic and prognostic tools in MPM.…”
Section: Introductionmentioning
confidence: 98%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…miR145-5p has been shown to act as a tumor suppressor in different tumor types (36). Its downregulation was associated with neoplastic cell growth, invasion, and metastasis and is paired with increased expression of different oncogenic mRNA targets expression, such as EGFR, MYC, MUC1, OCT4, and RTKN (8,36,43).…”
Section: Discussionmentioning
confidence: 99%
“…4,5). There is a growing consensus that miRNA downregulation has a profound impact on the genesis of tumors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%